Injection of Autologous Blood versus Corticosteroid for Lateral Epicondylitis: A Randomised Controlled Study. (December 2014) - Arik, Hasan Onur; Kose, Ozkan; Guler, Ferhat; Deniz, Gokmen; Egerci, Omer Faruk; Ucar, Mehmet
Purpose: To compare the efficacy of autologous blood injection versus corticosteroid injection for lateral epicondylitis. Methods: 21 men and 59 women (mean age, 45.2 years) presenting with lateral epicondylitis were randomised to receive either autologous blood injection (2 ml of autologous venous blood mixed with 1 ml of 2% prilocaine hydrochloride) or corticosteroid injection (1 ml of 40 mg methylprednisolone acetate mixed with 1 ml of 2% prilocaine hydrochloride) given by a single physician. Patients were assessed before (day 0) and after (days 15, 30, and 90) treatment for elbow pain (using a visual analogue scale [VAS]), function (using the patient-rated tennis elbow evaluation [PRTEE] questionnaire), and grip strength (using a hydraulic hand dynamometer). Patients were followed up at 6 months by telephone to assess elbow pain using the VAS. Results: No complications (infection, skin atrophy, neurovascular damage, or tendon rupture) were noted. 10 patients reported increased pain for up to 2 days after autologous blood injection. In both groups, the VAS score for elbow pain, PRTEE score, and grip strength improved significantly after treatment (p=0.0001), but the pattern of improvement differed. Compared with autologous blood injection, corticosteroid injection improved all 3 scores at a faster rate over the first 15 days (p=0.0001), and then started to decline slightly until day 90. After autologous blood injection, all 3 scores improved steadily and were eventually better (p=0.0001). If a 37% decrease in PRTEE is defined as complete recovery, 38 (95%) of patients with autologous blood injection and 25 (62.5%) of patients with corticosteroid injection achieved complete recovery (p=0.0001). Conclusion: Autologous blood injection was more effective over the follow-up period than corticosteroid injection in improving pain, function, and grip strength. It is recommended as a first-line injection treatment because it is simple, cheap, and effective.